Agronomic Characteristics, Physiology, and Antioxidant Activity of Shallots (Allium ascalonicum L.) in Response to Application of Chicken Manure and ZA Fertilizer in Floating Cultivation - Suci septrianda Suci; Susilawati susilawati; Irmawati Irmawati (Journal of Smart Agriculture and Environmental Technology, 2025)
Floating cultivation is an innovative techniques that enables optimal plant growth on flooded land. This system is particularly suitable for shallot plants, which are susceptible to waterlogging, as it can prevent root asphyxiation, improve aeration, and optimize yields in flood-prone areas. This study aimed to examine the effect of chicken manure and ZA fertilizer on the agronomic characteristics, physiological responses, and antioxidant activity of shallots (Allium ascalonicum L.) grown using a floating cultivation system. The research was conducted from July to September 2024 in the Kertapati District, Palembang, South Sumatra. A Factorial Randomized Block Design (FRBD) was used, with two factors : chicken manure (0, 1, 2, and 3 kg/plant) and ZA fertilizer (0, 2.00, 5.00, and 7.00 g/plant). Observed parameters included leaf length, number of leaves, number of tillers, wet stover weight, wind-dried tuber weight, fresh tuber weight, tuber diameter, chlorophyll content, and flavonoid content. The results showed that the application of 2 kg chicken manure and 5.00 g/plant of ZA fertilizer significantly improved leaf length, number of leaves, tiller formation, tuber yield, biomass production, and flavonoid content. Additionally, chicken manure enhanced soil fertility and nutrient uptake, while ZA fertilizer supported chlorophyll synthesis and antioxidant activity. In the floating cultivation system, the combination of these two treatments produced synergistic effects that optimized shallot growth and quality.